Current Indications for Transcatheter Mitral Valve Replacement Using Transcatheter Aortic Valves: Valve-in-Valve, Valve-in-Ring, and Valve-in-Mitral Annulus Calcification. Issue 2 (12th January 2021) - Urena, Marina; Vahanian, Alec; Brochet, Eric; Ducrocq, Gregory; Iung, Bernard; Himbert, Dominique
Abstract : Use of transcatheter mitral valve replacement (TMVR) using transcatheter aortic valves in clinical practice is limited to patients with failing bioprostheses and rings or mitral valve disease associated with severe mitral annulus calcification. Whereas the use of valve-in-valve TMVR appears to be a reasonable alternative to surgery in patients at high surgical risk, much less evidence supports valve-in-ring and valve-in-mitral annulus calcification interventions. Data on the results of TMVR in these settings are derived from small case series or voluntary registries. This review summarizes the current evidence on TMVR using transcatheter aortic valves in clinical practice from the characteristics of the TMVR candidates, screening process, performance of the procedure, and description of current results and future perspectives. TMVR using dedicated devices in native noncalcified mitral valve diseases is beyond the scope of the article. Abstract : Supplemental Digital Content is available in the text.